2015
DOI: 10.1136/emermed-2015-204681.2
|View full text |Cite
|
Sign up to set email alerts
|

BET 2: Should we use an age adjusted D-dimer threshold in managing low risk patients with suspected pulmonary embolism?

Abstract: A shortcut review was carried out to establish whether a higher age related threshold can be used when using d-dimer as a rule out test for pulmonary embolism. 29 papers were found of which 13 presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. The clinical bottom line is that in older patients suspected of having a Pulmonary Embolus (PE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Some advocate that D‐dimer testing should be entirely avoided in the elderly , but the effect of this approach would be that patients had to undergo imaging techniques instead, even if the probability of VTE were low. Age‐adjusted cut‐offs have been previously validated and recommended in DVT and PE to increase specificity in older patients while preserving sensitivity. However, this has been questioned , and a recent Cochrane review of D‐dimer to rule out pulmonary embolism did not find enough evidence to recommend age‐adjusted cut‐offs .…”
Section: Introductionmentioning
confidence: 99%
“…Some advocate that D‐dimer testing should be entirely avoided in the elderly , but the effect of this approach would be that patients had to undergo imaging techniques instead, even if the probability of VTE were low. Age‐adjusted cut‐offs have been previously validated and recommended in DVT and PE to increase specificity in older patients while preserving sensitivity. However, this has been questioned , and a recent Cochrane review of D‐dimer to rule out pulmonary embolism did not find enough evidence to recommend age‐adjusted cut‐offs .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that age-adjusted D-dimer reference ranges have higher sensitivity and specificity for PE [19][20][21][22] . This is particularly in the context of a low pre-test probability 23 .…”
Section: Discussionmentioning
confidence: 99%